2022
DOI: 10.21203/rs.3.rs-1368157/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of Online Learning on Sense of Belonging Among First Year Clinical Health Students During COVID-19: Student and Academic Perspectives

Abstract: Background The need to belong is a fundamental human desire that provides the basis for relationships and community; it provides a sense of security that enables growth and development. This sense of belonging is pivotal to new University students, indeed, without it, students are at greater risk of failing or withdrawing from their studies. Yet developing a sense of belonging within a new cohort is complex and multi-faceted and further complicated by a sudden shift from face-to-face to online learning. Our s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 18 publications
0
2
1
Order By: Relevance
“…Data revealed that students' sense of belonging, measured across four different subscales -perceived peer support, perceived classroom comfort, perceived isolation, and perceived faculty support -did not differ between students in a blended classroom and students in a virtual classroom. Our results contrast previous reports that online learners experience reduced social connection, interaction, and sense of belonging compared to face-to-face learners (Tang et al, 2022;Tratnik et al, 2019). Moreover, online learners had previously commented a sense of belonging is arguably more important when learning occurs remotely rather than in-person, as online learners are separated from the physical space and not afforded as many opportunities to socialize (Peacock et al, 2020).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Data revealed that students' sense of belonging, measured across four different subscales -perceived peer support, perceived classroom comfort, perceived isolation, and perceived faculty support -did not differ between students in a blended classroom and students in a virtual classroom. Our results contrast previous reports that online learners experience reduced social connection, interaction, and sense of belonging compared to face-to-face learners (Tang et al, 2022;Tratnik et al, 2019). Moreover, online learners had previously commented a sense of belonging is arguably more important when learning occurs remotely rather than in-person, as online learners are separated from the physical space and not afforded as many opportunities to socialize (Peacock et al, 2020).…”
Section: Discussioncontrasting
confidence: 99%
“…For example, many elements of the Community of Inquiry framework, particularly social presence (e.g., emotional expression, group cohesion, open communication), are found in our Inquiry course; therefore, it is possible these elements contributed to the increased sense of belonging among both student groups in our study (Garrison et al, 1999;The Community of Inquiry, n.d.). If this is the case, implementing inquiry-based approaches into courses, especially ones that are delivered virtually, seems important, as sense of belonging has been associated with better learning outcomes and increased retention rates (Banks & Dohy, 2019;Meehan & Howells, 2019;Tang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This unexpected change allowed little time for proper transition of in-class material to online learning with many faculty making few changes to their content as they scrambled to get online (Moore et al, 2021). Faculty reported a lack of institutional infrastructure and a lack of knowledge on the technical aspects of teaching online (Caliskan et al, 2020;El-Soussi, 2022;Salarvand et al, 2023) as well as elevated work demands and a prevailing state of fatigue (Tang et al, 2023). Some lost their professional identity as they had to adjust their beliefs related to online teaching and change their practices to adapt to this new learning environment (El-Soussi, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…This rapid transition had students concerned about how the course would be delivered and this uncertainty created additional stress (Dennen et al, 2022;Tang et al, 2023). This was understandable as many were not experts in online course content creation and delivery (Bailey and Lee, 2020;Moore et al, 2021).…”
Section: Introductionmentioning
confidence: 99%